2014
DOI: 10.35790/ecl.2.3.2014.6342
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENSI TINGKAT KECEMASAN PADA PASIEN INFARK MIOKARD LAMA DI POLIKLINIK JANTUNG RSUP PROF. Dr. R.D. KANDOU

Abstract: Lifestyle change affects the disease patterns from infection and malnutritions to degenerative diseases such as heart and vascular diseases. National prevalence of heart diseases in Indonesia is 7.2 percents and the prevalence in North Sulawesi is 8.2 percents. Myocardial infarction is usually followed by psychological reactions such as anxiety and depression. Anxiety has relation with heart disease progression and higher anxiety level increases the heart disease risk. This study aimed to know the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…The age of the respondents provides an illustration that the elderly age group (60-74 years) is the largest group of respondents who experience anxiety, which is 30 respondents (53.57%). The findings of this study are consistent with the findings of Maendra et al (2014), who found that respondents aged 66-75 years were the most likely to respond, accounting for 20 of the 60 total respondents (Maendra et al, 2014). A younger person is more likely to experience anxiety than an older person (though this can also be reversed).…”
Section: Age Of Respondentsupporting
confidence: 90%
“…The age of the respondents provides an illustration that the elderly age group (60-74 years) is the largest group of respondents who experience anxiety, which is 30 respondents (53.57%). The findings of this study are consistent with the findings of Maendra et al (2014), who found that respondents aged 66-75 years were the most likely to respond, accounting for 20 of the 60 total respondents (Maendra et al, 2014). A younger person is more likely to experience anxiety than an older person (though this can also be reversed).…”
Section: Age Of Respondentsupporting
confidence: 90%
“…Penelitian ini sejalan dengan penelitian yang dilakukan oleh Fadli, dkk (2020) yang menunjukan bahwa ada pengaruh yang signifikan antara usia dengan tingkat kecemasan tenaga kesehatan. Menurut I Ketut Maendra (2014), usia berkaitan dengan kedewasaan berpikir individu. Dengan usia yang lebih matang seseorang cenderung lebih dewasa dalam menghadapi masalah.…”
Section: Pembahasan 1 Pengaruh Usia Dengan Tingkat Kecemasan Tenaga K...unclassified
“…The level of anxiety experienced mainly by patients with CHD is severe anxiety at 34.78 % (6). Environmental factors cause that anxiety in CHD sufferers, and the most common anxiety experienced is moderate anxiety, reaching 93.3 % (7). Anxiety responses in feelings of fear, worry, discomfort, and other unclear feelings can be caused by self-talk with negative sentences and the lack of self-awareness (8).…”
Section: Introductionmentioning
confidence: 99%